PENINGKATAN KEMAMPUAN MOTORIK KASAR ANAK USIA 3 - 4 TAHUN MELALUI PERMAINAN ENGKLEK DI POS PAUD TERPADU MADANI SURABAYA - RODIYAH . (Universitas Narotama, 2020)
This study aims to improve the process and outcomes of learning as an effort to improve gross motor skills on Early Childhood at PPT Madani Surabaya. This research is a classroom action research conducted in the third cycle, the subjects in this study is a on Early Childhood PPT Madani Suabay academic year 2018/2019. The 15 Early Childhood consisting of 11 men and 4 women. Data collected through the performance, observation and documentation. Data analysis techniques done by using simple descriptive statistics, the data were analyzed quantitatively and qualitatively. The results of this study bring addressing the gross motor skills of early childhood can be enhanced through the traditional hopscotch game. The increase in gross motor skills of Early Childhood in its entirety before any action to increase from 44.4% with unfavorable category, to 55% with the category enough in the first cycle, being 93.3% with both categories at the second cycle. Keyword: Early Childhood, Gross Motor Skill, Engklek Traditional Games